COVID-19 as infodemic : the impact of political orientation and open-mindedness on the discernment of misinformation in WhatsApp - Pontes, Andressa Alves Bonafé (2021)
Messaging applications are changing the communication landscape in emerging countries. While offering speed and affordability, these solutions have also opened the way for the spread of misinformation. Aiming to better understand the dynamics of COVID-19 as infodemic, we asked Brazilian participants (n=1007) to report the perceived accuracy of 20 messages (10 true and 10 false). Each message was randomly presented within five fictitious WhatsApp group chats of varying political orientation. Correlational analyses revealed that right-wing participants had lower levels of truth discernment as did those with greater trust in social media as a reliable source of coronavirus information. Conversely, open-minded thinking about evidence and trust in the WHO and traditional media was positively associated with truth discernment. Familiarity with the content consistently increased perceived truthness for both true and false messages. Results point to the nefarious effects of COVID-19 politicization and underline the importance of promoting the ability to recognize and value new evidence as well as enhancing trust in international agencies and traditional media.